Fusion peptide induced modification of membrane organization and dynamics: Implications in developing fusion inhibitors - Smruti Mishra; Manbit Subhadarsi Panda; Hirak Chakraborty (Chemical Physics Impact, 2023)
An essential step in the entrance of enveloped viruses such as coronaviruses, the human immunodeficiency virus, and influenza is membrane fusion. A unique class of glycoprotein found on the viral envelope, known as a fusion protein, is responsible for catalyzing the fusion between the viral envelope and the host cell. Efforts have been made to block the fusion vis-à-vis the entry process by inactivating the fusion protein utilizing peptides and small molecules. Interestingly, the fusion proteins do not have any structural and sequence homology across viruses, and this limited the use of inhibitory peptides against a specific virus causing a paucity of immediate solutions against emerging and re-emerging viral diseases. Therefore, research has been initiated to develop broad-spectrum fusion inhibitors that can be effective to inhibit the entry of many viruses. In this review, we have examined the mechanistic details of membrane fusion and the potential significance of lipid composition. Moreover, we discussed the rationale for developing peptide-based, broad-spectrum fusion inhibitors that target membrane physical characteristics instead of fusion protein inactivation.